Photocatalytic Approach to α,α-Difluoroalkyl Alcohols - Kachkovskyi, Georgii; Cieślak, Marcin; Graczyk, Piotr; Zawadzki, Przemysław; Kalinowska-Tłuścik, Justyna; Werłos, Mateusz (Synthesis, 2022)
A convenient approach to previously poorly accessible α,α-difluoroalkyl alcohols by visible light-mediated photocatalysis was developed. Broad scope of the transformation together with experimental simplicity and scalability using flow techniques open good prospects for further studies of properties (including biological) of these novel products.
Keywords: fluorinated alcohols; photocatalysis; visible light; decarboxylation; N-acyloxyphthalimides; difluoroalkenes